STUDY OF RATIONAL PRESCRIBING AND DISPENSING OF PRESCRIPTIONS WITH NONSTEROIDAL ANTI-INFLAMMATORY DRUGS IN ORTHOPEDIC OUTPATIENT DEPARTMENT - Ingle, Pravinkumar; Patil, Prakash H; Lathi, Vibhavari (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: To study the prescribing pattern of non-steroidal anti-inflammatory drugs (NSAIDs) in outpatient orthopedic hospitals from a rural area of Maharashtra, India. Methods: A total of 237 prescriptions containing NSAIDs evaluated for their distribution according to the classification of NSAIDs and World Health Organization core indicators for prescribing practices and patient care. Results: The average number of drugs per prescription was 3.5. The average number of NSAIDs per prescription found to be 1.12. The incidence of generic prescribing was very low. The overall average consultation time and dispensing time found to be 4.5 and 1.9 minutes respectively. The percentage of drugs adequately labeled was 61.44%. Out of the 843 drugs, 267 were systemic NSAIDs, of which 50.56% and 49.43% used as monotherapy and fixed dose combinations respectively. The prescriptions are containing either one or two NSAIDs. Non-selective NSAIDs most commonly prescribed than selective cyclooxygenase-2 (COX2) inhibitors and highly selective COX2 inhibitors. The ratio of non-selective to selective NSAID usage pattern was 1:1.28. Conclusion: The study shows more use of traditional NSAIDs and underutilization of COX2 inhibitors. The study suggests that there is the immense scope of improvement for prescribing in the hospitals. Keywords: Prescribing pattern of non-steroidal anti-inflammatory drugs, Rational use of non-steroidal anti-inflammatory drugs, World Health Organization core drug use indicators.